Diagnosis and management of acute rheumatic fever - Irma Kartika; Syafarinah Nur Hidayah Akil (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Acute rheumatic fever is a nonsuppurative, immune-mediated consequence of group A streptococcal pharyngitis. Recurrent or severe acute rheumatic fever can cause permanent cardiac valve damage and rheumatic heart disease. Universally, the most common major manifestations during the first episode of ARF remain carditis and arthritis. Subclinical carditis now can fulfils a major criterion for ARF in all populations as in revised Jones criteria – AHA 2015. Many of the clinical features of ARF are non-specific, so a wide range of differential diagnoses should be considered. Primary prevention requires accurate recognition and proper antibiotic treatment of GAS pharyngitis. Prevention of recurrent attacks of rheumatic fever (secondary prevention) is the most cost-effective way of preventing further rheumatic heart disease (RHD). Penicillin remains the antibiotic of choice. Intramuscular penicillin is preferred as it is more effective than oral penicillin and results in better compliance.